Differences in self-assembly of spherical C60 and planar PTCDA on rippled graphene surfaces. (April 2019) - Li, Yanlong; Liu, Xiaoyang; Chen, Chuanhui; Duchamp, James; Huang, Rong; Chung, Ting-Fung; Young, Maxwell; Chalal, Tarek; Chen, Yong P.; Heflin, James R.; Dorn, Harry C.; Tao, Chenggang
Abstract: It was recently recognized that two-dimensional (2D) graphene exhibits nonplanar aberrations such as a rippled surface. Understanding the self-assembly of organic semiconductor molecules on monolayer 2D curved graphene surfaces is a paramount issue for ultimate application in semiconductor and optoelectronic devices. Herein, we report on the preparation of fullerene, C60 and perylenetetracarboxylic dianhydride (PTCDA) molecules adsorbed on a rippled graphene surface. We find that the spherical C60 molecules form a quasi-hexagonal close packed (hcp) structure, while the planar PTCDA molecules form a disordered herringbone structure. These 2D layer systems have been characterized by experimental scanning tunneling microscope (STM) imaging and computational density functional theory (DFT) approaches. The DFT computational results exhibit interaction energies for adsorbed molecule/rippled graphene complexes located in the 2D graphene valley sites that are significantly larger in comparison with adsorbed idealized planar/molecule graphene 2D complexes. In addition, we report that the adsorbed PTCDA molecules prefer different orientations when the rippled graphene peak regions are compared to the valley regions. This difference in orientations causes the PTCDA molecules to form a disordered herringbone structure on the rippled graphene surface. The results of this study clearly illustrate significant differences in C60 and PTCDA molecular packing on rippled graphene surfaces. Graphical abstract: Image 1